A Structured Review Addressing the Use of Radiographic Measures of Alignment and the Definition of Acceptability in Patients with Distal Radius Fractures. (December 2015) - Lalone, Emily A.; Grewal, Ruby; King, Graham J. W.; MacDermid, Joy C.
Background: Standard radiographs are routinely used in clinical care to characterize the severity of a distal radius fracture and to monitor patients following a distal radius fracture. The objective of this review was to describe the range and variability of radiographic measures described in the literature in patients following a distal radius fracture. Methods: A structured literature review was conducted using the Embase and PubMed databases. Inclusion criteria included full-text publications which employed radiographic measures to examine 100 or more participants following a distal radius fracture. A standardized data extraction form was used to identify study design, fracture classification systems, the types of and definitions of radiographic measurements, and acceptability criteria following distal radius fractures. Results: From an initial 263 studies, 31 studies were included in the final data extraction process. A narrative synthesis of the articles included in this review indicated that there was a set of commonly used radiographic measurements examined in patients with a distal radius fracture which included radial inclination, volar/dorsal tilt, intra-articular step/gap, and a measure of ulnar variance/radial shortening. While 52 % of studies referenced or published a standardized measurement technique, there was substantial variability in the actual description of each radiographic measurement performed. Conclusions: Substantial variability in how radiographic measurements are defined in large clinical studies as seen in this review suggest a need for consensus on the assessment and interpretations of radiographic measures used in patients following a distal radius fracture. Guidelines for radiographic measures should be established to ensure consistency between research and treatment centers.